Faktor-Faktor Penentu Nilai Perusahaan dalam Perspektif Teori Sinyal - Arum Pujiastuti; Faza Muhammad Sukarsono; Jaka Nugraha; Bima Yatna Anugerah Ramadhani (Pajak dan Manajemen Keuangan, 2025)
This study aims to analyze the effect of capital structure, firm growth, audit quality, and foreign ownership on firm value, proxied by Price to Book Value (PBV), in consumer cyclical sector companies listed on the Indonesia Stock Exchange during 2018–2022. The analytical method used is panel data regression with the Random Effect Model (REM) approach. The results show that capital structure has a positive and significant effect on firm value. Conversely, firm growth, audit quality, and foreign ownership do not significantly affect firm value. These findings support signaling theory, which suggests that the use of debt within a reasonable threshold can boost investor confidence and enhance firm value. Therefore, it is recommended that corporate management focus on optimizing capital structure rather than relying solely on firm growth or external factors such as audit quality or foreign investors to improve firm value.